Intrinsic factors, release conditions and presence of conspecifics affect post‐release dispersal after translocation of Iberian ibex. (22nd January 2021) - Garnier, A.; Besnard, A.; Crampe, J. P.; Estèbe, J.; Aulagnier, S.; Gonzalez, G.
Abstract: Translocation is an important tool in restoring biodiversity, particularly when species have been extirpated from an area. In the period just after release, the main objective of conservation managers is to keep as many of the translocated individuals in the release area as possible, in order to maximize the number of founders of the new population. Environmental and intrinsic factors, release conditions and social behaviour are likely to influence an individual's propensity to move away from the release site (known as post‐release dispersal); however, few studies have explored the relative importance of these factors. The aim of this study was to evaluate how these four factors affected the post‐release dispersal of 169 Iberian ibex translocated from Spain to the French Pyrenees. We modelled the linear distance between the barycentre of each individual ibex's monthly locations and the release site. Our results indicated that most individuals stayed close to the release site, but that inter‐individual variability was high. Post‐release dispersal was higher for males than females, with male breeders exhibiting higher exploration behaviour than juveniles. Release season played a major role, with dispersal being the lowest in spring and the highest during the rutting period. Dispersal was also found to be lower when conspecifics were present in the release area, probably due to their role as a cue for favourable habitat. These findings can be used by conservation managers to inform translocation strategies in order to enhance success: for example by releasing females and young males in spring and splitting a reintroduction project into successive release operations. Abstract : The aim of this study was to evaluate how environmental conditions, intrinsic factors, release conditions and social behaviour affected the post‐release dispersal of 169 Iberian ibex translocated from Spain to the French Pyrenees. Distance from the release site was sex and age dependent, season of the release and presence of conspecifics playing also a major role. These findings can be used by conservation managers to inform translocation strategies in order to enhance success.